Recursos didácticos tecnológicos educativos en el área de estudios sociales para mejorar el aprendizaje en los estudiantes de la Escuela Mariana Riera de Troya de la Parroquia Febres Cordero, cantón Babahoyo de la Provincia de Los Ríos - Fernández Casis, Daniel Stalin (2019)
The use of Teaching and Learning resources is a principle of all practice in the classroom that the teacher performs, as well as determining the domains of learning, but selecting and / or evaluating a didactic resource is a very procedural task because of its structuring your result will depend on the classroom. An institution committed to its educational quality, is one that has an organization and institutional management of innovative teaching and learning resources, where students can develop skills based on ICT, for which teachers must learn how to teach and facilitate knowledge in the subject of social studies. So it is very significant to study the case on Educational Technology Educational Resources in the area of Social Studies to improve learning in the students of the school "Mariana Riera de Troya" of the parish Febres Cordero, Babahoyo canton of the province of Los Rios , knowing that a student knows very well to read and interpret a book, map, map, meaning of a city or archaeological site, a work of art, because a historical event within a period or cycle, among other things., because this also to be a domain in the student and professional, are elements that a human being manages in a country or region that is developed, and this makes them have a sense of development and contribution to culture by science. For this it is necessary to use the innovative technological didactic resources which can now be designed and implemented for the teaching of the social sciences and are very valuable, because they seek to generate critical thinking in the student. Interactive methods are key in education and everything in the social sciences, so that ICT are fundamental for the design of innovative didactic resources that facilitate their teaching by the teacher and the apprehension on the part of the student.